Urban shrinkage, industrial renewal and automotive plants. - Luescher, Andreas; Shetty, Sujata (Palgrave Macmillan, 2019)
Das Buch beschreibt am Beispiel der Städte Janesville (Wisconsin), Willow Run (Michigan), Bochum und Genk die Beziehung zwischen Industrieansiedlungen der Automobilindustrie und der bebauten Umwelt auf mehreren Ebenen. Aus verschiedenen Perspektiven, einschließlich Architektur, Städtebau und Stadtplanung, untersuchen die Autoren die sich ändernde Form der Autofabrik selbst, die sich ändernde Geographie der Automobilproduktion und die Herausforderungen, denen sich die Kommunen durch den Wegzug dieser Industrie stellen müssen. Die Folgen von Werksstilllegungen für Stadtentwicklung und städtische bzw. lokale Identität werden untersucht.

This book focuses on the relationship between the auto industry and the built environment at multiple scales, a topic of particular interest now as the industry is going through a period of major transformation. Drawing from multiple perspectives, including architecture, urban design and urban planning, the authors examine the changing form of the auto factory itself, the changing geography of auto production, and the challenges faced by communities as the auto plants that once brought them prosperity, and often a sense of identity, leave town. They examine four places that are dealing in different ways, and with varying success, with the aftermath of a decommissioned auto plant in their midst. These are Janesville, Wisconsin, and Willow Run, Michigan, in the United States, and Bochum, Germany, and Genk, Belgium, in Europe. Together these four cases provide some clues about what the future might look like for places that were once intimately connected with the manufacture of cars.
Keywords: Industriestadt; Industrieregion; Automobilindustrie; Altindustrie; Schließung; Betriebsstilllegung; Wirkungsanalyse; Raumwirksamkeit; Schrumpfung; Stadtentwicklung; Lokale Identität; Industriegebäude; Nutzungsänderung; Städtevergleich; Internationaler Vergleich